Quality of life of caregivers of patients with gastrointestinal cancer: relationship of sex, age, and stage of the cancer patients - Lilian Nascimento Rosa; Nora Manoukian Forones (Brazilian Journal of Oncology)
Introduction: The caregivers of cancer patients may experience changes in their routine that affect their quality of life. The aim of the study was to identify the domains that compromise the quality of life (QoL) of the caregivers of patients with gastrointestinal cancer (GIC).